PERAN MANAJEMEN KEUANGAN DI SDN CILEGON 2 DALAM MENINGKATKAN INOVASI KEUANGAN DI DUNIA PENDIDIKAN - Yustiva, Fitriyatul; Yusuf, Furtasan Ali; Hayadi, B. Herawan; Rahmulyana, Anjar; Hendrawati, Tuti; Masquroh, Hayatul (Bhinneka Multidisiplin Journal, 2024)
This research aims to explore the role of financial management at the Cilegon 02 State Elementary School (SDN) in increasing financial innovation in the education sector. Through a qualitative approach, data was collected from in-depth interviews with school administrators and analysis of related documents. The findings show that effective financial management at SDN Cilegon 02 has a positive impact in increasing financial innovation, enabling wise allocation of funds and increasing the efficiency of use of financial resources. These results strengthen understanding of the importance of transparency, accountability and thorough financial planning in improving the quality of education. The implications of this research include encouraging the adoption of effective financial management practices in other schools as well as strengthening policies that support transparency and accountability in the management of education funds